A Return to State-Led Integrated Regional Planning? Emerging Approaches from Three U.S. States. (June 2020) - Green, Timothy; Finn, Donovan
After decades of neglect, several U.S. states have increased support for regional development planning, creating new programs, organizations, and funding streams to support it. Analysis of programs in three states (New York, Michigan, and Indiana) shows similarities among them as well as contrasts with prior episodes of state-led regional planning. The new programs deliberately sidestep older regional planning organizations like COGs and RPCs in favor of new organizations with larger roles for the private sector and greater access to public funds. The resulting plans focus on individual projects within a pro-development agenda, but still have potential to coordinate action at a regional scale.